The Effects of Individualized Low- and Moderate-Load Circuit Training on Physical Performance, Hormonal Responses, And Hematological Adaptations in Resistance-Trained Men. - Peng, Wuwen; Qu, Wenhao; Lu, Di; Sun, Jian; Li, Duanying (Journal of Sports Science & Medicine, 2026)
This study aimed to compare the effects of low-load circuit training (LL-CT) and moderate-load circuit training (ML-CT) on physical performance adaptations, hormonal responses, and hematological parameters in resistance-trained men. Thirty-two resistance-trained males (age 20.31 ± 1.00 y) were randomly assigned to three groups: LL-CT (n = 11), ML-CT (n = 11), or CON (n = 10). Participants in the training groups performed two sessions per week for 8 weeks. Both protocols consisted of four rounds of five exercises in a circuit format with a 30 s work:30 s rest duty cycle and 2-min inter-set rest. Exercise intensity was prescribed as 30% 1RM (LL-CT) or 70% 1RM (ML-CT), where 1RM was determined for four lifts: power clean, back squat, bench press, and deadlift. Loads during each exercise were expressed as a percentage of that exercise's own 1RM. Pre- and post-intervention measures included one-repetition maximum in the back squat and bench press (kg); countermovement jump and squat jump height (cm); 30-m sprint time (s); 505 change-of-direction time (s); peak power (W) and relative peak power (W⋅kg-1); and maximal oxygen uptake VO2max (mL⋅kg-1⋅min-1). Blood samples were collected to analyze resting hormone levels and hematological profiles. Both the LL-CT and ML-CT groups showed significant improvements in 1RM, CMJ, SJ, 30-m sprint, 505 agility, PP, and VO2max (p < 0.05), whereas the CON group only improved in squat 1RM (p<0.05). No significant differences were observed in RPP across all three groups (p>0.05). Between-group comparisons revealed that only 1RM showed significant superiority in the training groups compared to CON (p<0.05), with no significant differences observed in other performance outcomes (p > 0.05). Both LL-CT and ML-CT resulted in significant increases in total testosterone (T) and mean corpuscular hemoglobin concentration (MCHC) (p<0.05), while only ML-CT showed a significant improvement in hemoglobin (HB). No significant changes were observed in red blood cell (RBC) count, white blood cell (WBC) count, red cell distribution width (RDW), or hematocrit (HCT) across groups. Under comparable hormonal responses and hematological adaptations, LL-CT demonstrated greater mechanical efficiency while achieving physical performance improvements equivalent to those of moderate-load training.